Progress and challenges in biomarker enrichment for cancer early detection. (14th September 2021) - Sinawang, Prima Dewi; Soto, Fernando; Ozen, Mehmet Ozgun; Akin, Demir; Demirci, Utkan
Abstract: Cancer cells generate and secrete diverse molecules into circulation that could be used as signatures for health and disease. A significant obstacle in detecting such molecules derives from their low signal-to-noise ratio in subsequent downstream analyses. Developing reliable tools and methods for cancer early detection is crucial for advancing global strategies to decrease mortality, monitor disease progression and therapy, and improve the quality of life of patients. This perspective critically addresses recent developments in cancer early detection, highlighting current trends in the enrichment of cancer-related biomarkers, dividing them into biochemical and biophysical methods. Finally, we provide insights into the challenges and opportunities in biomarker isolation and enrichment protocols. Integrating these methods into clinical decision-making pipelines could lead to a better understanding of cancer progression, treatment efficacy, and hence improving the medical outcomes for cancer patients.